An Algorithmic Theory of the Choice of Techniques - Bidard, Christian (Econometrica, 1990)
The author builds a theory of the choice of techniques in joint production, at a given profit rate, considering a market algorithm. Partial results are extended by means of an abstract notion of technology, where techniques meet demand and satisfy local properties. Global results on the existence, uniqueness, and convergence towards an equilibrium technique are obtained. The author, thus, characterizes cases where a square technique is reached, which provides an answer to an old debate, initiated by W. S. Jevons, between classical and neoclassical economists. But the framework allows for a more general interpretation in terms of two-level planning procedures. Copyright 1990 by The Econometric Society.